SEJARAH MATEMATIKA DI CHINA - Aulia Azzahra; Aditiya Nasocha Prasetiyo; Rizqi Fadlilah; Ahmad Faridh Ricky Fahmy (UPT Penerbitan Universitas Jember, 2022)
The author would like to convey about the history of mathematics in China, what were the discoveries of the Chinese at this time for the society centered there, Legend states that this emperor ordered the burning of all books from the previous period to suppress dissent, but there are several reasons to doubt that this actually done This work, called the Suan shu shu (Book of Numbers and Calculations), is the earliest surviving Chinese text on mathematics. Like much of his later work, it consists of problems and their solutions, some of them: which we will consider below. An incomplete version of this set exists from the Song dynasty, printed in 1213, and a more complete version from the Ming dynasty, printed in 1403-1407. Exam systems often require reading the relevant sections of math texts, as well as solving problems in the same way as those described in these texts. This article is written with the study of literature with the aim of knowing the history of mathematics in China and its writing. Keywords: China, history, mathematics